Peran Komitmen Organisasi Dan Efikasi Diri Pada Organizational Citizenship Behavior - Cyndee Maretta Lisette Anggraini; Anwar Mansyur (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the significance of organizational commitment and self efficacy on organizational citizenship behavior at BPSDMD Central Java Province. This research uses a quantitative approach and uses a sample of 43 respondents. The sampling technique used in this research is purposive sampling. While the analysis technique uses multiple linear regression analysis which is equipped with instrument testing, model testing, and hypothesis testing using SPSS 25 software. The result of this study indicate that organizational commitment has a significant effect on organizational citizenship behavior and self efficacy has no significant effect on organizational citizenhip behavior. Keywords: Organizational Commitment, Self Efficacy, Organizational Citizenhsip Behavior